2018
DOI: 10.15537/smj.2018.11.23299
|View full text |Cite
|
Sign up to set email alerts
|

Natural cycle versus hormone replacement therapy cycle in frozen-thawed embryo transfer

Abstract: Objectives:To compare implantation rates, clinical pregnancy rates and live birth rates associated with natural and hormone replacement therapy (HRT) methods of endometrial preparation in frozen-thawed embryo transfer (FET) cycles.Methods:The results of 108 natural cycles and 224 HRT cycles of FET transfers performed in a private in vitro fertilization (IVF) center between June 2013 and August 2015 were retrospectively compared with respect to implantation rate, clinical pregnancy rate, and live birth rate.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…After adjusting for factors that differed in the baseline data, the logistic regression model showed that the HRT group was equally likely to have a clinical pregnancy ( P =0.728) and a live birth ( P =0.758) similar to the NC group. This is consistent with the findings of several previous retrospective cohort studies that compared the NC and HRT groups and discovered that the two groups had similar clinical pregnancy and live birth rates [15–17] . However, a previous retrospective study has shown that the miscarriage rate in the HRT group is higher than in the NC group, which may be related to the higher proportion of patients with polycystic ovary syndrome in the HRT group [18] .…”
Section: Discussionsupporting
confidence: 92%
“…After adjusting for factors that differed in the baseline data, the logistic regression model showed that the HRT group was equally likely to have a clinical pregnancy ( P =0.728) and a live birth ( P =0.758) similar to the NC group. This is consistent with the findings of several previous retrospective cohort studies that compared the NC and HRT groups and discovered that the two groups had similar clinical pregnancy and live birth rates [15–17] . However, a previous retrospective study has shown that the miscarriage rate in the HRT group is higher than in the NC group, which may be related to the higher proportion of patients with polycystic ovary syndrome in the HRT group [18] .…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have found no significant differences in the CPR, IR, or LBR between the HRT and natural cycles in FET[ 31 33 ]. However, we found that although no significant difference was observed in the CPR of HRT cycles or natural cycles, HRT cycles were associated with a higher EMR, which is consistent with the findings reported by Maria et al In their prospective study, they observed a higher miscarriage rate in the HRT group[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of 33 studies also reported no statistically significant difference in clinical pregnancy or live birth between natural cycles without hCG triggering (based on spontaneous serum LH peak monitoring) versus modified natural cycles with hCG triggering ( 148 ). In addition, when an hCG trigger in a natural cycle (144 embryos transferred in 108 cycles) was compared with hormone therapy (357 embryos transferred in 224 cycles) at a single IVF centre, in women undergoing frozen embryo transfer, no significant differences were reported between the groups in implantation rate, clinical pregnancy rate or live birth rate ( 149 ).…”
Section: Results Of the Consensus And Actionable Recommendations (Including Supportive Evidence)mentioning
confidence: 99%